2008
DOI: 10.1097/olq.0b013e31815d968d
|View full text |Cite
|
Sign up to set email alerts
|

From the NIH: Proceedings of a Workshop on the Importance of Self-Obtained Vaginal Specimens for Detection of Sexually Transmitted Infections

Abstract: On June 27, 2006, the NIH conducted a workshop to review published data and current field practices supporting the use of self-obtained vaginal swabs (SOVs) as specimens for diagnosis of sexually transmitted infections (STIs). The workshop also explored the design of studies that could support FDA clearance of SOVs for STI testing, particularly for specimens collected in nonclinical settings including patients' homes. This report summarizes the workshop findings and recommendations. Participants concluded that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 68 publications
(70 reference statements)
1
77
0
1
Order By: Relevance
“…For women, vaginal swabs may be preferred over FCU specimens for this type of screening (26). This and many other studies have demonstrated that self-collected vaginal swabs are suitable specimens for chlamydia and gonorrhea testing by NAATs, and their use has been recommended by the NIH and the CDC (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For women, vaginal swabs may be preferred over FCU specimens for this type of screening (26). This and many other studies have demonstrated that self-collected vaginal swabs are suitable specimens for chlamydia and gonorrhea testing by NAATs, and their use has been recommended by the NIH and the CDC (17).…”
Section: Discussionmentioning
confidence: 99%
“…While such samples collected at home are not yet FDA cleared, self-obtained vaginal swabs collected in a clinic are FDA cleared for one type of NAAT (26). We therefore decided to compare the performances of the three commercially available NAATs for C. trachomatis and N. gonorrhoeae testing with vaginal samples obtained at home through an Internet screening program and mailed in a dry state (10,17,29) to the laboratory for testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15 Self-taken vaginal swabs are an acceptable and accurate specimen type for chlamydia testing using NAAT techniques. 16 Instructions for males described how to collect a urine sample. Both sets of instructions were pre-tested with young people and modified according to feedback received.…”
Section: Development Of Home Sample Collection Kitsmentioning
confidence: 99%
“…However, SOVS specimens are FDA cleared for use only when collected in a clinic setting. The ability to self-collect at home and mail in specimens could have a significant impact on sexually transmitted disease (STD) control efforts (13)(14)(15). To assess such use in screening programs, we initially performed a pilot study to determine specimen stability and monitor the shipping temperatures during transit.…”
mentioning
confidence: 99%